Review of mass media effect in inter-cultural communication - Bata Gouda Mohamed Hawali; Dietrich Cyrielle (International Journal of Communication and Society, 2020)
This paper aims to describe how humans communicate with each other is always influenced or in a complex cultural context. Humans learn to think, feel, believe, and work on what is culturally appropriate. Language, friendship, eating habits, communication practices, social actions, economic and political activities, and technology are based on cultural patterns. This paper is the result of library research, where the author conducts academic studies of various relevant reading material. The conclusion in this paper is What people do, how they act, how they live and communicate, are responses to and functions of their culture.